Puréed Foods: High Protein - Jamila R. Lepore; Wendy J. Dahl (EDIS)
Protein is an important nutrient. Many older adults do not consume enough of this vital nutrient, crucial to overall health and well-being. For those with dysphagia and on a puréed diet, consuming sufficient protein is even more difficult. While a texture-modified diet may not be the diet of choice, the goal is to make it as appealing as possible so that the person consuming the purées can experience a better quality of life. This 4-page fact sheet was written by Jamila R. Lepore and Wendy J. Dahl and published by the UF Department of Food Science and Human Nutrition, March 2013. http://edis.ifas.ufl.edu/fs208